2019
DOI: 10.1038/s41366-019-0436-7
|View full text |Cite
|
Sign up to set email alerts
|

Reduced SIRT1 and SIRT2 expression promotes adipogenesis of human visceral adipose stem cells and associates with accumulation of visceral fat in human obesity

Abstract: Background/Objectives: The histone deacetylases SIRT1 and SIRT2 have been shown to be involved in the differentiation of rodent adipocyte precursors. In light of the differences in gene expression and metabolic function of visceral (V) and subcutaneous (S) adipose tissue (AT) and their resident cells, the aim of this study was to investigate the role of SIRT1 and SIRT2 in the differentiation of adipose stem cells (ASCs) isolated from SAT and VAT biopsies of non-diabetic subjects with varying levels of BMI.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 49 publications
(77 reference statements)
5
49
0
Order By: Relevance
“…Activated PPARa increased Lpl expression to decompose TG into fatty acids, and elevated Cpt-1a, Mcad, Lcad, and Acox1 expression to accelerate fatty acid oxidation. The mRNA expression of SIRT1 was decreased in WAT of diabetic SD rats and IR-3T3-L1 adipocytes, it is consistent that reduced expression of SIRT1 in human obesity may foster visceral adipose tissue expansion (Perrini et al, 2020). GQD also increased the expression of histone deacetylase SIRT1, which may inhibit adipocyte differentiation including PPARg adipogenesis activity and initiate a broad program of mitochondrial gene expression and thermogenesis (Tang, 2016).…”
Section: A B Cmentioning
confidence: 64%
“…Activated PPARa increased Lpl expression to decompose TG into fatty acids, and elevated Cpt-1a, Mcad, Lcad, and Acox1 expression to accelerate fatty acid oxidation. The mRNA expression of SIRT1 was decreased in WAT of diabetic SD rats and IR-3T3-L1 adipocytes, it is consistent that reduced expression of SIRT1 in human obesity may foster visceral adipose tissue expansion (Perrini et al, 2020). GQD also increased the expression of histone deacetylase SIRT1, which may inhibit adipocyte differentiation including PPARg adipogenesis activity and initiate a broad program of mitochondrial gene expression and thermogenesis (Tang, 2016).…”
Section: A B Cmentioning
confidence: 64%
“…We then evaluated the effect of metformin and vitamin D in the modulation of epigenetic genes, HDAC1 and Sirtuins. Other authors previously described that reduced HDAC1, SIRT1, and SIRT2 expression promotes adipogenesis and accumulation of visceral fat in human obesity [ 46 , 47 ]. Here, we show that ADSC exposure to metformin and vitamin D increases the expression of all the above-mentioned epigenetic modulators ( Figure 3 ), suggesting their involvement in blocking adipogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Some others found by snRNA-seq SIRT2 expression level is extremely high in some specific groups of cells in the cancer tissues with SIRT2-low expression level in general. 17 Studies have found that SIRT2 is highly expressed in renal cancer cells, and patients with higher levels of SIRT2 have a worse prognosis than patients with lower levels of SIRT2 expression. SIRT2 can promote tumor cells to form clumps, so tumor cells are more resistant to fluorescenceinduced apoptosis, and after kidney transplantation, patients with high levels of SIRT2 expression are less likely to have tumor recurrence than those with SIRT2 expression Patient is taller.…”
Section: Expression Of Sirtin Tumorsmentioning
confidence: 99%